The Expression of “Enak” (Delicious) For Food In Social Media Instagram - Khusnul Khatimah; Rawinda Fitrotul Mualafina; Cut Irna Liyana (Universitas Teuku Umar, 2021)
The purpose of this study is to describe the form of expressions “enak” (delicious) in Instagram social media and the function of using these forms. The method used is a descriptive qualitative method with data collection techniques in the form uninvolved conversation observation technique on the use of expressions “enak” on several Instagram accounts. The results obtained are (a) the form of “enak” expressions is in the form of standard expressions, religious sentences, prefixes ter- and se- in the form of slang, and hyperbolic expressions; (b) the function of using this form is to promote food products, create a contemporary impression, and provide a more concrete picture.